Pengaruh Pengetahuan Ibu terhadap Kejadian Anemia pada Ibu Hamil di Puskesmas Gandapura: Studi Observasional Analitik - Nurul Huda (NAJ Nursing Applied Journal, 2025)
Anemia in pregnant women is a significant global public health issue, with a prevalence of 35.5% in 2023, according to the Global Anemia Estimates 2025 from the World Health Organization (WHO). The prevalence of anemia among reproductive-aged women is 30.7%, while it is 30.5% in non-pregnant women. This indicates that anemia is more prevalent among pregnant women compared to the general female population, highlighting the need for greater attention to this health issue. This study aims to identify and evaluate the risk factors or causes of anemia in pregnant women using an observational analytical approach. The research design employed is cross-sectional, which allows for the observation of the relationship between maternal knowledge about anemia and the occurrence of anemia in pregnant women at the same point in time. The study population consists of all pregnant women who visit the community health center (Puskesmas) for checkups. The results indicate that there is no significant relationship between parity (number of previous births) and the occurrence of anemia in pregnant women, with an Odds Ratio (OR) of 1.58. This means that women with higher parity are 1.58 times more likely to experience anemia compared to women with lower parity. However, the study found a significant relationship between maternal knowledge about anemia and the occurrence of anemia in pregnant women. Mothers with better knowledge about anemia are less likely to experience it. This study is expected to provide important information about the importance of improving maternal knowledge regarding anemia, which can contribute to the prevention and control of anemia in pregnant women. By enhancing maternal knowledge, it is hoped that the prevalence of anemia in pregnant women can be reduced, improving the overall health of both mothers and their unborn children.